The Analysis Of Moral Value And Character In Novel “Negeri 5 Menara” By Ahmad Fuadi - Hasby, Asrul; Islami, M. Jagat (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
This research is descriptive method. By employing descriptive method, this research was trying to present an analysis of moral value and character in novel Negeri 5 Menara novel by Ahmad Fuadi. Most of the data taken from books and internet references. It aims at finding out the differences between the major character and the minor character and the moral value. This study is structural analysis by employing descriptive method approach. This research is expected to be able to identify the specific differences between the major character and the minor character and the moral value. Hopefully the writer is able to identify some differences of the major and minor characters and find the moral value of the novel. As the result of this research we can identify some character differences. In factual, the major character and the minor character are found in Negeri 5 Menara novel, but they have some differences themselves. And also the moral value is found. There were six major characters as the protagonist that were grouped into “Sahibul Menara”. They were Alif Fikri, Raja Lubis, Said Jufri, Dulmajid, Atang Yunus, and Baso Salahuddin. The other characters in the novel were minor characters, such as Ayah, Amak, Kiai Rais, Ustad Salman, and Tyson. The differences between the major characters and the minor characters in the novel were the major characters that took some important role in the story and the minor characters who did not take important role. The minor characters appeared only to support the major characters even though the minor characters showed up some times. The moral values which could be taken from the novel “Negeri 5 Menara” were sincerity, patience, honesty, and leadership as characterized in the novel. Finally the writer suggests to readers especially English literature students to conduct more research for understanding the analysis of protagonist character.